Periprocedural Pain and Outcome Difference of Local Anesthetic vs Mechanodesensitization During Lumbar Facet Blocks for Low Back Pain. Issue 10 (29th May 2020) - Aleem, Bilal; Mubashir, Muhammad Muslim; Clark, Erin; Vardeh, Daniel
Abstract: Objective: To compare periprocedural pain from mechanodesensitization (MD) with local anesthetic (LA) during medial branch blocks (MBBs), with a secondary outcome to compare diagnostic responses during the five hours postprocedure. Methods: Forty-four patients with low back pain underwent three level bilateral MMBs. For the LA technique, 0.5 mL of 1% lidocaine was injected subcutaneously on one side, and for MD the skin was stretched using the index finger and thumb on the other. A 25-gauge 3.5-inch spinal needle was inserted over each target area, and the periprocedural pain was recorded on the numeric rating scale (NRS). After fluoroscopic positioning, the patient's side preference was recorded. Patients were discharged with a pain diary to record pain scores every 30 minutes for five hours. Results: Despite reporting higher pain scores with LA vs MD ( P = 0.0462, mean difference ± SEM = 0.4924 ± 0.2459), global comparison favored LA. Pain scores with LA dropped from an average baseline of 6.11 to a mean NRS ± SEM of 2.461 ± 0.615, and with MD from 6.11 to 2.599 ± 0.552 ( P ≤ 0.001). While there was no significant difference in area under the curve comparison over five hours ( P = 0.3341), there was a trend toward lower pain scores with LA use. Conclusions: LA before needle insertion for MBBs appears to be more painful compared with MD. Additionally, subcutaneously administered local anesthetic may have a therapeutic effect on nonspecific low back pain, resulting in a potentially false-positive test in the evaluation of lumbar facet pain.